2022
DOI: 10.3389/fpls.2022.966495
|View full text |Cite
|
Sign up to set email alerts
|

Field rice panicle detection and counting based on deep learning

Abstract: Panicle number is directly related to rice yield, so panicle detection and counting has always been one of the most important scientific research topics. Panicle counting is a challenging task due to many factors such as high density, high occlusion, and large variation in size, shape, posture et.al. Deep learning provides state-of-the-art performance in object detection and counting. Generally, the large images need to be resized to fit for the video memory. However, small panicles would be missed if the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In addition, while previous works mainly relied on larger backbone networks or higher-resolution input images to achieve higher accuracy, balancing all dimensions of network width/depth/resolution is crucial when considering both accuracy and efficiency (Tan and Le, 2019;Dollaŕ et al, 2021;Tan and Le, 2021;Wang et al, 2022). Recent studies have shown that carefully designed lightweight networks can achieve comparable performance to their heavy counterparts with much less computational cost (Howard et al, 2017;Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while previous works mainly relied on larger backbone networks or higher-resolution input images to achieve higher accuracy, balancing all dimensions of network width/depth/resolution is crucial when considering both accuracy and efficiency (Tan and Le, 2019;Dollaŕ et al, 2021;Tan and Le, 2021;Wang et al, 2022). Recent studies have shown that carefully designed lightweight networks can achieve comparable performance to their heavy counterparts with much less computational cost (Howard et al, 2017;Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The field is mainly divided into two-stage algorithms represented by Faster Region-based Convolutional Neural Network (Faster RCNN) (Chen and Gupta, 2017) and one-stage algorithms represented by You Only Look Once (YOLOv3) (Redmon and Farhadi, 2018). Among them, CenterNet (Duan et al, 2019), EfficientDet (Tan et al, 2020), RetinaNet (Lin et al, 2017), Yolov7-tiny (Wang et al, 2022) have achieved SOTA performance in many different fields.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were difficulties in actual field testing for mobile applications. Wang et al (2022b) proposed a new method to remove repeated detections and achieved an accuracy of 92.77%. The methods, however, need to be optimized for UAV images and different density identification.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were difficulties in actual field testing for mobile applications. Wang et al. (2022b) proposed a new method to remove repeated detections and achieved an accuracy of 92.77%.…”
Section: Introductionmentioning
confidence: 99%
“…At present, convolutional neural networks (CNN) are increasingly and widely used for plant and animal image detection ( Liu and Wang, 2020 ; Peng and Wang, 2022 ; Wang et al, 2022 ). The secondary detector represented by R-CNN for fast extraction and learning of image features was applied to the automated detection of batch images.…”
Section: Introductionmentioning
confidence: 99%